2020
DOI: 10.1177/2319714520972210
|View full text |Cite
|
Sign up to set email alerts
|

Sub-prime Crisis or COVID-19: A Comparative Analysis of Volatility in Indian Banking Sectoral Indices

Abstract: Stock market volatility may be a function of company, industry, or world over information made public. The present study has investigated the volatility of Indian banking sectoral indices with the general banking index for two shocking events: the Sub-prime crisis and COVID-19. A comparative analysis of both the shocks leading to these indices’ volatility has been conducted using symmetric and asymmetric models. This study’s findings show that these indices’ volatile behaviour has been strong enough to persist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 52 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Figure 7 shows the co-occurrence analysis of author keywords between 2011 and 2022. The figure shows that some themes emerge through the graphical mapping, such as COVID-19 (Bhatia & Gupta, 2020), pandemic, entrepreneurship, attitude, trust, emotional intelligence, sustainable intelligence, corporate governance, etc. The figure demonstrates the interdisciplinary focus of the journal.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the co-occurrence analysis of author keywords between 2011 and 2022. The figure shows that some themes emerge through the graphical mapping, such as COVID-19 (Bhatia & Gupta, 2020), pandemic, entrepreneurship, attitude, trust, emotional intelligence, sustainable intelligence, corporate governance, etc. The figure demonstrates the interdisciplinary focus of the journal.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Figure 7 shows the co-occurrence analysis of author keywords between 2011 and 2022. The figure shows that some themes emerge through the graphical mapping, such as COVID-19 (Bhatia & Gupta, 2020), pandemic, entrepreneurship, attitude, trust, The co-citation analysis of the authors has been done to understand the most cited authors in FBR. The network diagram has been developed with a threshold of 20 papers with 29 connections.…”
Section: Most Contributing Authors Institutions and Countries Of Fbr ...mentioning
confidence: 99%
“…As per the study by Bhatia and Gupta (2020), Indian banking sector oral indicators were compared to the overall banking index using asymmetric and symmetric models, taking into account the Sub-prime crisis and COVID-19. Researchers found that despite the leverage impact that occurred during the sub-prime crisis, these indexes' volatility characteristics were sufficient to maintain their market presence.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A higher degree of uncertainty can cause financial volatility, a measure of dispersion around the mean return of a financial asset (Bonga, 2014). As Bhatia and Gupta (2020) indicate, stock market volatility may be a composite of companies, industries, or the world over information that has been made public. In support, Alqaralleh and Canepa (2021) narrate that the COVID-19 outbreak triggered massive spikes in uncertainty in world financial markets.…”
Section: Introductionmentioning
confidence: 99%
“…A health crisis like the current pandemic can alter and change the nature of a stock return's volatility and hence has to be verified for investment decisions and policy. As Bhatia and Gupta (2020) argue, stock returns may have turned volatile due to panics brought by the pandemic stock, and the volatility may be country-specific. A study by Mahonye and Mandishara (2014) shows that both global and local economic factors determine stock market returns.…”
Section: Introductionmentioning
confidence: 99%